Just‐in‐Time to Save Lives: A Pilot Study of Layperson Tourniquet Application. (20th August 2015) - Goolsby, Craig; Branting, Andrew; Chen, Elizabeth; Mack, Erin; Olsen, Cara; Cone, David C.
Abstract Objectives The objective was to determine whether just‐in‐time (JiT) instructions increase successful tourniquet application by laypersons. Methods This was a randomized pilot study conducted in August 2014. The study occurred at the Uniformed Services University campus in Bethesda, Maryland. A total of 194 volunteers without prior military service or medical training completed the study. The participant stood in front of a waist‐down mannequin that had an exposed leg. An observer read a scenario card aloud that described a mass casualty event. The observer then asked the participant to apply a Combat Application Tourniquet (C‐A‐T) to the mannequin. Test participants received a 4 × 6‐inch card, with JiT instructions, in addition to their C‐A‐T; controls received no instructions. Participants were randomized in a 3:1 ratio of instructions to no instructions. The study's primary outcome was the proportion of successfully applied tourniquets by participants receiving JiT instructions compared to participants not receiving instructions. Secondary outcomes included the time for successful tourniquet placement, reasons for failed tourniquet application, and participants' self‐reported willingness and comfort using tourniquets in real‐life settings. Results Just‐in‐time instructions more than doubled successful tourniquet placement. Participants supplied with JiT instructions placed a tourniquet successfully 44.14% of the time, compared to 20.41% of the time for controls without instructions (risk ratio = 2.16; 95% confidence interval = 1.21 to 3.87; p = 0.003). Conclusions Just‐in‐time instructions increase laypeople's successful application of C‐A‐T. This pilot study provides evidence that JiT instructions may assist the lay public in providing effective point‐of‐injury hemorrhage control.